Characterization of genetic determinants of the resistance to phylloxera, Daktulosphaira vitifoliae, and the dagger nematode Xiphinema index from muscadine background - Rubio, Bernadette; Lalanne-Tisné, Guillaume; Voisin, Roger; Tandonnet, Jean-Pascal; Portier, Ulysse; Van Ghelder, Cyril; Lafargue, Maria; Petit, Jean-Pierre; Donnart, Martine; Joubard, Benjamin; Bert, Pierre-François; Papura, Daciana; et al. (BMC plant biology, 2020)
Muscadine (Muscadinia rotundifolia) is known as a resistance source to many pests and diseases in grapevine. The genetics of its resistance to two major grapevine pests, the phylloxera D. vitifoliae and the dagger nematode X. index, vector of the Grapevine fanleaf virus (GFLV), was investigated in a backcross progeny between the F1 resistant hybrid material VRH8771 (Vitis-Muscadinia) derived from the muscadine R source 'NC184-4' and V. vinifera cv. 'Cabernet-Sauvignon' (CS). In this pseudo-testcross, parental maps were constructed using simple-sequence repeats markers and single nucleotide polymorphism markers from a GBS approach. For the VRH8771 map, 2271 SNP and 135 SSR markers were assembled, resulting in 19 linkage groups (LG) and an average distance between markers of 0.98 cM. Phylloxera resistance was assessed by monitoring root nodosity number in an in planta experiment and larval development in a root in vitro assay. Nematode resistance was studied using 10-12 month long tests for the selection of durable resistance and rating criteria based on nematode reproduction factor and gall index. A major QTL for phylloxera larval development, explaining more than 70% of the total variance and co-localizing with a QTL for nodosity number, was identified on LG 7 and designated RDV6. Additional QTLs were detected on LG 3 (RDV7) and LG 10 (RDV8), depending on the in planta or in vitro experiments, suggesting that various loci may influence or modulate nodosity formation and larval development. Using a Bulked Segregant Analysis approach and a proportion test, markers clustered in three regions on LG 9, LG 10 and LG 18 were shown to be associated to the nematode resistant phenotype. QTL analysis confirmed the results and QTLs were thus designated respectively XiR2, XiR3 and XiR4, although a LOD-score below the significant threshold value was obtained for the QTL on LG 18. Based on a high-resolution linkage map and a segregating grapevine backcross progeny, the first QTLs for resistance to D. vitifoliae and to X. index were identified from a muscadine source. All together these results open the way to the development of marker-assisted selection in grapevine rootstock breeding programs based on muscadine derived resistance to phylloxera and to X. index in order to delay GFLV transmission.